Tailoring the Porous Structure of Mono‐dispersed Hierarchically Nitrogen‐doped Carbon Spheres for Highly Efficient Oxygen Reduction Reaction. Issue 1 (20th July 2020) - Shu, Chengyong; Gan, Zhuofan; Hou, Yuyang; Zhu, Ting; Ma, Jijun; Tang, Wei; Wu, Yuping
Abstract : The search for a low‐cost metal‐free cathode material with excellent mass transfer structure and catalytic activity in oxygen reduction reaction (ORR) is one of the most challenging issues in fuel cells. In this work, nitrogen‐rich m‐phenylenediamine is introduced into the synthesis of porous carbon spheres to tune the pore structure and nitrogen‐doped active sites. As a result, more pyridinic N and pyrrolic N functional species were observed at the interior and surface of the carbon spheres. The introduction of m‐phenylenediamine also regulated the nucleating of precursors, an urchin‐like mesoporous surface structure ensures point contact and less agglomeration between each particle was obtained. With optimized proportion of micropores/mesopores and improved nitrogen‐contained functional species, the ORR activity can be remarkably improved. The half‐wave potential of this catalyst could achieve to 0.81 V (versus RHE) which is only 42 mV lower than commercial Pt/C catalyst. Furthermore, the optimized cathode catalyst achieved a 69 mW cm −2 maximum power density when operated in direct methanol fuel cells at room temperature. Abstract : Urchin‐like mesoporous nitrogen‐doped carbon spheres as highly efficient ORR catalysts for direct methanol fuel cells.